Double-negative B cells and DNASE1L3 colocalise with microbiota in gut-associated lymphoid tissue - Montorsi, Lucia; Pitcher, Michael J.; Zhao, Yuan; Dionisi, Chiara; Demonti, Alicia; Tull, Thomas J.; Dhami, Pawan; Ellis, Richard J.; Bishop, Cynthia; Sanderson, Jeremy D.; Jain, Sahil; D’Cruz, David; et al. (Nature Communications, 2024)
Intestinal homeostasis is maintained by the response of gut-associated lymphoid tissue to bacteria transported across the follicle associated epithelium into the subepithelial dome. The initial response to antigens and how bacteria are handled is incompletely understood. By iterative application of spatial transcriptomics and multiplexed single-cell technologies, we identify that the double negative 2 subset of B cells, previously associated with autoimmune diseases, is present in the subepithelial dome in health. We show that in this location double negative 2 B cells interact with dendritic cells co-expressing the lupus autoantigens DNASE1L3 and C1q and microbicides. We observe that in humans, but not in mice, dendritic cells expressing DNASE1L3 are associated with sampled bacteria but not DNA derived from apoptotic cells. We propose that fundamental features of autoimmune diseases are microbiota-associated, interacting components of normal intestinal immunity.
CRIS-Team Scopus Importer:2024-05-24